1986
DOI: 10.1139/v86-167
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between cations and sugars. II. Enthalpies, heat capacities, and volumes of aqueous solutions of Ca2+D-ribose and Ca2+D-arabinose at 25 °C

Abstract: . 64, 996 (1986).The thermodynamic parameters characterizing the interaction between Ca2+ and the suitably positioned sequences of hydroxyls of some sugar isomers have been determined. This was done by comparing the properties of D-ribose which bears such sequences of hydroxyls with the properties of D-arabinose chosen as an inactive reference. The enthalpies of solution and of dilution, the apparent molal heat capacities, and the apparent molal volumes of the two pentoses have been first measured in water at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Morel and co-workers [42][43][44][45][46][47][48][49], Wang and co-workers [50][51][52][53][54][55][56][57][58][59][60][61], and Hernandez-Luis et al [62,63] used the transfer functions approach and reported a very comprehensive set of data for the interaction parameters of sugars with several electrolytes.…”
Section: Empirical Virial Expansionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morel and co-workers [42][43][44][45][46][47][48][49], Wang and co-workers [50][51][52][53][54][55][56][57][58][59][60][61], and Hernandez-Luis et al [62,63] used the transfer functions approach and reported a very comprehensive set of data for the interaction parameters of sugars with several electrolytes.…”
Section: Empirical Virial Expansionsmentioning
confidence: 99%
“…The AGCM (eqs. [43][44][45][46] was tested by Matveev et al [75] for polysaccharides such as amylose, amylopectin, dextran, and pullulan. The parameter 〈T gh -1 〉 was fixed at 0.2028 10 -3 K -1 for all the polysaccharides, while 〈T gd -1 〉 ranges from 0.29 K -1 (dextran and pullulan) to 0.31 K -1 (amylose and amylo pectin).…”
Section: Glass Transition Predictions Of Saccharide Aqueous Solutionsmentioning
confidence: 99%
“…The hydration characteristics of saccharides (1)(2)(3)(4)(5)(6) and their interactions with electrolytes and nonelectrolytes (7)(8)(9)(10)(11)(12)(13)(14)(15) in aqueous media are of significant biological and thermodynamic importance. It has been widely reported (16)(17)(18)(19)(20)(21)(22) that sugars and polyols act as efficient stabilizing agents for proteins/enzymes because of their ability to enhance the structure of water.…”
Section: Introductionmentioning
confidence: 99%
“…A similar correlation was also found by Morel and co-workers between h ES (CaCl 2 -saccharide) and Ts ES (CaCl 2 -saccharide), as well as h ES (KCl-saccharide) and Ts ES (KCl-saccharide) parameters for some monosaccharides. 37 …”
Section: Discussionmentioning
confidence: 99%